The presidential fringe : questing and jesting for the Oval Office - Stein, Mark, 1951- (Potomac Books, an imprint of the University of Nebraska Press, 2020)
In examining over thirty unlikely presidential candidates from the past two centuries, Mark Stein reveals how fringe candidates have impacted the nation's political landscape.